Optimalisasi Perencanaan Instalasi Pengolahan Air Limbah (IPAL) Kegiatan Industri Rumah Potong Ayam (RPA) PT X Di Daerah Jombang - Nurilita Amalia Cahyani; Tuhu Agung Rachmanto (Pusat Riset dan Inovasi Nasional, 2024)
The industrial activities of chicken slaughterhouse and meat processing by PT X generate waste that needs to be treated through a Wastewater Treatment Plant (WWTP) during the operational processes. However, the WWTP of PT X indicates a need for improvement in wastewater treatment performance to optimize the reduction of pollutant parameters in the wastewater generated by PT X’s industrial operations. The performance evaluation of PT X’s WWTP is conducted by examining technical aspects, ensuring that the WWTP can operate optimally, and the effluent wastewater meets the standard quality requirements. Therefore, the quality of the effluent can be assured to protect the sustainability of natural resources in the surrounding area, especially the water resources in the vicinity of PT X’s industrial activities. Based on the technical analysis results, the optimization of treatment standards at PT X’s Wastewater Treatment Plant (WWTP) is planned by adding an Biofilter Aeration unit to ensure that the quality of the generated waste meets the standards.